Franchise Entrepreneurial Leadership: Leadership Dominance and Its Level of Success at the Franchisee Level - Cary, John C. (Journal of Leadership, Accountability and Ethics, 2020)
Entrepreneurs within the United States are plagued with high incidences of failure in the early years of business. What seems to be lacking in these organizations is leadership and the type of leadership style that leads to greater levels of success. This quantitative study answered the following research question: Is there a significant relationship between the various degrees of success of selected national franchises and the assessed leadership styles of their leaders? The leadership styles assessed were transformational and transactional. A random sample of 50 franchise leaders throughout the United States was selected and the data was collected from a Multifactor Leadership Questionnaire. The findings showed that there was a significant difference in styles, indicating that transformational leadership delivers greater levels of success at the franchisee level.